Example of applying a Health, Safety and Environment management system in cetacean research: Case study from a satellite tagging field accident - Hassel, Lucas B.; Zerbini, Alexandre Novaes; Andriolo, Artur; Cabete, Ricardo (J. Cetacean Res. Manage., 2022)
Satellite telemetry is a powerful method to study the movements and habitat use of cetaceans. The deployment of transmitters is usually conducted using remote techniques and involves close approaches to the target animals. The present study reports on an accidental collision between a female humpback whale and an inflatable boat, which occurred on 7 October 2010 off the coast of Brazil. At the time of the accident, the boat was occupied by four crew members: the tagger, the photographer, the driver and an observer. This collision resulted in head trauma and severe brain injury to the photographer. It also resulted in changes of the tagging deployment procedures and the implementation of a Health, Safety and Environment (HSE) management system. The objective of this work is to report on this accident and describe procedures adopted to assess and minimise risks. Changes and updates in deployment protocols are viewed as improvements to minimise accidents during marine mammal tagging operations. Some of these improvements were also discussed and implemented by other organisations. Accidents such as the one reported here can and should be prevented. However, when they occur, they provide an opportunity to assess and correct unanticipated deficiencies in field work procedures.